Феноменологічний аналіз кримінальної агресії - Гладкова, Є. О.; Gladkova, Ye. O.; ORCID: http://orcid.org/0000-0003-4621-1738; ResearcherID: I-7032-2016 (Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 75-82, 2017)
Статтю присвячено аналізу визначення, елементів та змісту кримінальної агресії. Розглянуто специфіку психологічних механізмів формування та розвитку різних типів агресивної поведінки.

Aggressive behavior is one of the most dangerous manifestations of human behavior as it is often reincarnated in diverse multi-action criminal acts, which undoubtedly are the results of the manifestation of certain personal characteristics of the individual. Considering this the most important is to study criminal aggression not only in theoretical aspect, but also to establish the factors (and, above all, psychological) affecting the mechanisms of aggressive behavior in order to develop adequate measures of prevention to protect individuals and society in the whole from this type of crime. Cognition of the essence and nature of aggressive criminal behavior is possible only in case, when the object of a comprehensive interdisciplinary phenomenological analysis of the relevant professionals is aggression as a personal trait of a man. Aggression should be distinguished from aggressiveness that is the form of behavior from the personality’s traits. Aggression – is a set of specific actions that cause damage to another object, and aggressiveness is provided by the person’s readiness, on whom the aggression is directed, to perceive and interpret the behavior of the aggressor in a proper way. In this sense, perhaps we can talk about the potentially aggressive perception and potentially aggressive interpretation as a stable personal trait of the view of life and worldview. Aggressiveness can be also understood as a person’s reaction to frustration of needs and conflict, expressed in subjective tendency to hostile behavior aimed at complete or partial restriction of liberty, actions, expression of will of another person or community, their management, inflicting damage or suffering. Separation of the concepts of “aggression” and “aggressiveness” leads to the formulation of a number of important conclusions. On the one hand, aggressiveness of a person as a trait is not really the object of any aggressive actions of a subject. On the other hand, human aggressiveness is not always manifested in clearly aggressive actions. Manifestation or non-manifestation of aggressiveness as a personal trait in specific acts of behavior is always the result of comprehensive interaction of trans-situational and situational factors. In case of aggressive actions of a non-aggressive person, a factor of the situation is the basis of the dominance of this system of actions. In case of aggressive actions of an aggressive person, the primacy belongs to personal qualities of this person. Criminal law and criminology mainly deal with the destructive (malignant) aggression, although the Criminal Code of Ukraine has Articles with criminal liability for the violence committed during the protection from the attack, but exceeding the limits of necessary defense or extreme necessity. Physical and verbal aggression committed for lucrative motives, is a mean of satisfying living individual needs, rather than implementation of destructive aspirations for destruction and ruin.

Статья посвящена анализу понятия, элементов и содержания криминальной агрессии. Рассмотрена специфика психологических механизмов формирования и развития разных типов агрессивного поведения.
Phenomenological analysis of criminal aggression
Феноменологический анализ криминальной агрессии
Гладкова, Є. О. Феноменологічний аналіз кримінальної агресії / Євгенія Олексіївна Гладкова // Вісник Кримінологічної асоціації України. - 2017. - № 1 (15). - С. 75-82.
Hladkova, Yu. O. (2017), “Phenomenological analysis of criminal aggression” [Fenomenolohichnyi analiz kryminalnoi ahresii], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 1, pp. 75–82.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінологічний аналіз; кримінальна агресія; насильство; особистість; протидія злочинності; запобігання злочинам; criminological analysis; criminal aggression; violence; personality; combating crime; prevention of crimes; агресія; агрессия; aggression; криминологический анализ; криминальная агрессия; насилие; личность; противодействие преступности; предупреждение преступлений